Między sportem a sztuką. Sylwetka Wiktorii Goryńskiej - Szajna, Gabriel (Wydział Sztuki UR, 2018)
The aim of this article is to show a theoretical perspective of humanistic anthropology of sport. It discusses the self-creation of Wiktoria Goryńska’s personality and her artistic work. The text looks at the symbiosis of art and sport, using a case study, an analysis of historical facts, a comparative method and an analysis of the literature on the subject. Presenting Goryńska in the sphere of her self-expression in art and sport proves that she was extremely active socially, pursuing the common good. She is an outstanding figure in Polish culture.
Between sport and art. Presenting Wiktoria Goryńska
Keywords: Wiktoria Goryńska; autokreacja; szermierka; sztuka w sporcie; self-creation; fencing; sport; art